2014
DOI: 10.1111/tri.12340
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evolution, secular trends, and risk factors of renal dysfunction following cardiac transplantation

Abstract: SummaryRecent reports suggest that individuals who underwent heart transplantation in the last decade have improved post-transplant kidney function. The objectives of this retrospective study were to describe the incidence and to identify fixed and time-dependent predictors of renal dysfunction in cardiac recipients transplanted over a 25-year period (1983-2008). To illustrate temporal trends, patients (n = 306) were divided into five groups based on year of transplantation. The primary endpoint was the estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Improved hemodynamic performance after heart transplantation often results in a short-term increase in renal function, but this is typically followed by a progressive decline over time (2). One in 10 heart transplant patients ultimately develop chronic renal failure (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved hemodynamic performance after heart transplantation often results in a short-term increase in renal function, but this is typically followed by a progressive decline over time (2). One in 10 heart transplant patients ultimately develop chronic renal failure (3).…”
Section: Introductionmentioning
confidence: 99%
“…One in 10 heart transplant patients ultimately develop chronic renal failure (3). Posttransplant renal deterioration is multifactorial in etiology, with pretransplant renal dysfunction (2,4), older age (2) and comorbidities such as diabetes (2,4) known to contribute, but long-term calcineurin inhibitor (CNI) therapy also plays an important role (3,5). A recent meta-analysis of randomized controlled trials in de novo and maintenance heart transplant patients found that reducing CNI exposure significantly improved posttransplant renal function (6).…”
Section: Introductionmentioning
confidence: 99%
“…As would be expected, patients with poor kidney function pretransplant are significantly more likely to show deteriorating renal function after heart transplantation . Other risk factors include older age and possibly the presence of diabetes or hyperglycemia .…”
Section: Impaired Renal Functionmentioning
confidence: 76%
“…By 10 years, chronic kidney disease stage 3A or worse is almost universal [19] and approximately 10% of heart transplant patients eventually progress to chronic renal failure [23]. As would be expected, patients with poor kidney function pretransplant are significantly more likely to show deteriorating renal function after heart transplantation [20,21,24]. Other risk factors include older age [21,25] and possibly the presence of diabetes or hyperglycemia [20,21].…”
Section: Impaired Renal Functionmentioning
confidence: 96%
“…If the GFR remains less than 45 despite attempts at improving renal dysfunction, proceeding with isolated HT may carry increased risk of worse survival and should be balanced by consideration of HKT in collaboration with transplant nephrologists versus continuation of LVAD support as destination therapy. If isolated HT in the setting of significant renal dysfunction is chosen, aggressive comorbidity management (diabetes and hypertension) delaying or minimizing calcineurin inhibitor use through induction therapy and innovative combinations of immunosuppressive therapy (and steroid minimization) should be considered [30].…”
Section: Renal Dysfunction and Posttransplant Outcomes: The Times Arementioning
confidence: 99%